Phenotypic and genotypic characteristics of Trueperella pyogenes isolated from ruminants - Rogovskyy, Artem S. (J Vet Diagn Invest, 2018)
Trueperella pyogenes is an opportunistic pathogen that causes suppurative infections in animals including humans. Data on phenotypic and genotypic properties of T. pyogenes isolated from ruminants, particularly goats and sheep, are lacking. We characterized, by phenotypic and genotypic means, T. pyogenes of caprine and ovine origin, and established their phylogenetic relationship with isolates from other ruminants. T. pyogenes isolates (n = 50) from diagnostic specimens of bovine (n = 25), caprine (n = 19), and ovine (n = 6) origin were analyzed. Overall, variable biochemical activities were observed among the T. pyogenes isolates. The fimbriae-encoding gene, fimE, and neuraminidase-encoding gene, nanH, were, respectively, more frequently detected in the large (p = 0.0006) and small (p = 0.0001) ruminant isolates. Moreover, genotype V (plo/nanH/nanP/fimA/fimC) was only detected in the caprine and ovine isolates, whereas genotype IX (plo/nanP/fimA/fimC/fimE) was solely present in the isolates of bovine origin (p = 0.0223). The 16S rRNA gene sequences of all T. pyogenes isolates were clustered with the reference T. pyogenes strain ATCC 19411 and displayed a high degree of identity to each other. Our results highlight phenotypic and genotypic diversity among ruminant isolates of T. pyogenes and reinforce the importance of characterization of more clinical isolates to better understand the pathogenesis of this bacterium in different animal species.